2006
DOI: 10.1093/toxsci/kfl155
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Damage Induced by Acrylamide and Glycidamide in Mammalian Cells: Correlation with Specific Glycidamide-DNA Adducts

Abstract: Acrylamide (AA) is a suspected human carcinogen generated in carbohydrate-rich foodstuffs upon heating. Glycidamide (GA), formed via epoxidation, presumably mediated by cytochrome P450 2E1, is thought to be the active metabolite playing a central role in AA genotoxicity. In this work we investigated DNA damage induced by AA and GA in mammalian cells, using V79 Chinese hamster cells. For this purpose, we evaluated two cytogenetic end points, chromosomal aberrations (CAs) and sister chromatid exchanges (SCEs), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 34 publications
7
42
0
Order By: Relevance
“…Compared to AA, GA (2-4 mM) was much more mutagenic, about 5-10-fold more potent. This is consistent with several previously reported genotoxicity studies conducted using mammalian cells (Baum et al, 2005;Besaratinia and Pfeifer, 2003;Koyama et al, 2006;Martins et al, 2006). Since the genotoxic responses at higher concentration are reproducible, LOH analysis of the mutants induced by 4 mM GA and 16 mM AA treatments was conducted to determine the types of the mutations.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Compared to AA, GA (2-4 mM) was much more mutagenic, about 5-10-fold more potent. This is consistent with several previously reported genotoxicity studies conducted using mammalian cells (Baum et al, 2005;Besaratinia and Pfeifer, 2003;Koyama et al, 2006;Martins et al, 2006). Since the genotoxic responses at higher concentration are reproducible, LOH analysis of the mutants induced by 4 mM GA and 16 mM AA treatments was conducted to determine the types of the mutations.…”
Section: Discussionsupporting
confidence: 89%
“…Those chromosomal mutations are most likely associated with GA-derived DNA adducts. A recent study shows that there is a strong correlation between the levels of N7-GA-Gua and the extent of sister-chromatid exchange induction in GA-treated V79 cells (Martins et al, 2006). It has been suggested that the clastogenicity results from formation of depurinating DNA lesions and the formation of DNA breaks when repairing the DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…c-mitosis) in the absence of metabolic activation (Baum et al, 2005;Koyama et al, 2006;Jiang et al, 2007;Martins et al, 2007;Katic et al, 2010;ATSDR, 2012;Pingarilho et al, 2013) (Table 21). GA induced also chromosomal aberrations, micronuclei or SCE (Table 21), however at lower concentrations that are not severely cytotoxic.…”
Section: Genotoxicitymentioning
confidence: 99%